House prices and affordability in Malaysia / Ashrof Zainuddin and Kamsiah Sirat - Zainuddin, Ashrof; Sirat, Kamsiah (Universiti Teknologi MARA, Perak, 2011)
The primary purpose of this study was to investigate the relationship between house prices in Malaysia and the macro and microeconomic factors influencing them. A review of literature supports that movement in house prices are influenced by a multitude of factors and these include movements in price of building and building materials, housing demand and supply, population growth, Consumer Price Index (CPI), Gross Domestic Product (GDP), Base Lending Rates (BLR) and the availability of complementary as well as substitute properties. The study attempts to examine the factors that correlate with house prices and then estimate future prices by applying the multi-regression pricing model which will incorporate those factors. The idea is that House Price Index (HPI) that corresponds to multi-dimensional attributes such as economic indicators can determine house prices in the future.